Determinants of Capital Structure of Consumer Goods Industry Sector Companies: Evidence from the Indonesian Stock Exchange - Nababan, Lambok; Lee, Jhason Kristian (Jurnal Bisnis Mahasiswa, 2025)
This research is motivated by the discrepancies and inconsistencies observed in prior investigations. This study aims to investigate the factors that influence the capital structure of firms in Indonesia. We employed the purposive sampling strategy to acquire 36 companies. The employed analytical technique is multiple linear regression with SmartPLS 4. This study reveals an inverse correlation between capital structure and profitability, as well as asset growth, the current ratio, and GDP. Conversely, capital structure exhibits a positive correlation with earnings volatility, asset tangibility, firm age, firm size, asset composition, inflation rate, and interest rate. We anticipate that future research will reassess the application of the same variables and those that exert no influence in our study. This research is limited to the consumer goods sector, and it is hoped that future research will consider other sectors. We advise prospective authors to use a 5% significance level and increase the sample size, whereas this study employs a 10% significance level. The findings of this study contribute to the accounting literature, particularly in the area of capital structure, and can serve as a reference for firm management to identify factors influencing capital structure. The results will enable firm management to enhance organisational performance and secure the company's viability.